El dominio letrado que persiste en la academia - Rezavala Zambrano, narcisa (2016)
This article analyzes the ways reading and writing are applied in daily practice in higher education. The questions that support this statement are: How do I do it? Why don’t the students participate in class? Which is the cause for students read little, they understand bad and they express muddled by written?. How do we lose the fear of our students to find a liberating education?. How do we achieve academic discourse to be appropriate to the profiles of each professional career? How do we encourage teachers to write about their subjects, scientific articles? To answer these questions, there was a case study done in the different faculties of the Laica Eloy Alfaro de Manabí University, finding that most of academics (literate) they do not contribute to critical analysis from their subjects, which prevents that students develop and upgrade their knowledge.